Biến đổi phương trình $-\sqrt{3}\sin x+\cos x=1$ về phương trình lượng giác cơ bản, ta được
$\sin\left(x-\dfrac{\pi}{6}\right)=\dfrac{1}{2}$ | |
$\sin\left(x-\dfrac{\pi}{6}\right)=1$ | |
$\sin\left(x+\dfrac{5\pi}{6}\right)=\dfrac{1}{2}$ | |
$\sin\left(\dfrac{\pi}{6}-x\right)=1$ |
Chọn phương án C.
Chia hai vế của phương trình cho $2$ ta được
\begin{eqnarray*}
&-\dfrac{\sqrt{3}}{2}\sin x+\dfrac{1}{2}\cos x&=\dfrac{1}{2}\\
\Leftrightarrow&\sin x\cos\dfrac{5\pi}{6}+\cos x\sin\dfrac{5\pi}{6}&=\dfrac{1}{2}\\
\Leftrightarrow&\sin\left(x+\dfrac{5\pi}{6}\right)&=\dfrac{1}{2}.
\end{eqnarray*}